Utility of the point of care CD4 analyzer, PIMA, to enumerate CD4 counts in the field settings in India - Thakar Madhuri; Mahajan Bharati; Shaikh Nawaj; Bagwan Salman; Sane Suvarna; Kabra Sandhya; Rewari Bharat; Shaukat Mohamad; Singh Namita; Trevor Peter; Paranjape Ramesh (AIDS Research and Therapy, 2012)
Abstract Background In resource limited settings non-availability of CD4 count facility at the site could adversely affect the ART roll out programme. Point of care CD4 enumerating equipments can make the CD4 count available at the site of care and improve the patients’ management considerably. This study is aimed at determining the utility of a Point of Care PIMA CD4 analyzer (Alere, Germany) in the field settings in India. Method The blood samples were collected from 1790 participants at 21 ART centers from different parts of the country and tested using PIMA and the reference methods (FACSCalibur, FACSCount and CyFlow SL3). The paired finger prick and venous blood samples from 175 participants were tested by the PIMA CD4 Analyzer and then by FACSCalibur. Result The CD4 counts obtained by PIMA CD4 analyzer showed excellent correlation with the counts obtained by the reference methods; for venous blood the Pearson’s r was 0.921, p < 0.001 and the relative bias was 0.2% (range: -42 to 42%) and for finger prick samples, the Pearson’s r was 0.856 and the relative bias was −9.1% (range: -46% to 27%). For CD4 ranges; <250, 251–350, 351–500 and >500 cells/mm3, the differences in the median CD4 counts obtained by the reference method and the PIMA analyzer were not significant (P > 0.05) and the relative bias were low (−7 to 5.1%). The Intermachine comparison showed variation within the acceptable limit of%CV of 10%. Conclusion In the field settings, the POC PIMA CD4 analyzer gave CD4 counts comparable to the reference methods for all CD4 ranges. The POC equipment could identify the patients eligible for ART in 91% cases. Adequate training is necessary for finger prick sample collection for optimum results. Decentralization of CD4 testing by making the CD4 counts available at primary health centers, especially in remote areas with minimum or no infrastructure would reduce the missed visits and improve adherence of the patients.